Sensitive Spectrophotometric Method for Determination of Chloramphenicol in Pharmaceutical Preparations Using 7,7',8,8'-tetracyanoquinodimethane reagent - Hayfa M. Al-Hammoshi Department of Chemistry; Theiaa Najm Al-Sabha (College of Education for Pure Sciences, 2013)
Abstract A simple, sensitive and rapid spectrophotometric method for the determination of chloramphenicol in pure as well as in dosage form is described. The method is based on the reaction of reduced chloramphenicol with 7,7',8,8'-tetracyanoquinodimethane (TCNQ) at pH10 to form an orange colored complex of maximum absorption peak (λmax) at 475 nm. Under the optimized reaction conditions, Beer's law correlating the absorbance with chloramphenicol concentration was obeyed in the range of 0.05-5 μg ml-1. The molar absorptivity was 1.51×105 L. mol−1cm−1. The limits of detection and quantitation were 0.028 and 0.323 μg ml-1, respectively. The accuracy and precision of the method were satisfactory; the average recovery was 100.12 % and relative standard deviation ≤0.7. The stoichiometry of the reaction was studied, and the reaction mechanism was postulated. The proposed method was successfully applied to the determination of chloramphenicol in its pharmaceutical capsule, syrup and ointment with good accuracy and precisions. The results obtained by the proposed method are compared with those obtained by the official method and other reported methods. Keywords: Spectrophotometry; Chloramphenicol; TCNQ; Pharmaceutical